The intervention of Nanotechnology against epithelial fungal diseases - Higa, Leticia Herminia (2013)
Fungal infections can attack epithelial tissues and, according to the immunological state of the patient, some of them invade deeper organs, becoming seriously life compromising. Besides, bloodstream and local infections associated with intravascular devices constitute a significant problem associated with increased mortality. Topical therapy is desirable since, in addition to targeting the site of infection, it reduces the risk of systemic side effects and increases patient compliance. In this review we describe the pros and cons of using nano-objects that being toxic in nature could be used to cover surfaces of medical devices, or can act as carriers for targeted delivery of antifungals to skin. Non-toxic nano-objects were also included because they improve the ocular delivery of antifungals, classically suffering from ineffective topical administration, difficult access for systemic medication or local invasive administration. The new preclinical developments of nanoparticulate agents against cutaneous and ocular mycosis are grouped in three main sections: (1) In vitro antifungal activity of metallic nanoparticles, (2) In vitro and in vivo antifungal activity of non metallic nanoparticles (3) Ocular delivery of non metallic nanoparticles.